Efektivitas Terapi Latihan Pada Pasien Stroke: Literature Review - Jihan Nur Afifah; Dini Nur Alpiah (JURNAL ILMIAH NUSANTARA, 2026)
Stroke leads to long-term disability affecting motor function, balance, fitness, and cognition. Exercise- and stimulation-based rehabilitation interventions have been widely applied in post-stroke recovery. To analyze the effectiveness of exercise and stimulation interventions in post-stroke patients based on randomized controlled trials (RCTs). This literature review applied the PICO approach and included ten RCT studies evaluating exercise, electrical stimulation, aerobic training, and balance interventions. Data were analyzed narratively by comparing intervention and control groups. The results show that the intervention groups demonstrated significantly greater improvements than control groups (p < 0.05) in spasticity reduction, motor function, balance, cardiorespiratory fitness, neuroplasticity, and cognitive outcomes. Multimodal interventions produced superior results compared to single interventions.